Modulating the catalytic activity of enzyme-like nanoparticles through their surface functionalization. Issue 5 (31st October 2017) - Cao-Milán, Roberto; He, Luke D.; Shorkey, Spencer; Tonga, Gulen Y.; Wang, Li-Sheng; Zhang, Xianzhi; Uddin, Imad; Das, Riddha; Sulak, Mine; Rotello, Vincent M.
Abstract : Surface functional groups of nanozyme ligands dictate their kinetic behavior. Abstract : The inclusion of transition metal catalysts into nanoparticle scaffolds permits the creation of catalytic nanosystems (nanozymes) able to imitate the behaviour of natural enzymes. Here we report the fabrication of a family of nanozymes comprised of bioorthogonal ruthenium catalysts inserted in the protective monolayer of gold nanoparticles. By introducing simple modifications to the functional groups at the surface of the nanozymes, we have demonstrated control over the kinetic mechanism of our system. Cationic nanozymes with hydrophobic surface functionalities tend to replicate the classical Michaelis Menten model, while those with polar groups display substrate inhibition behaviour, a key mechanism present in 20% of natural enzymes. The structural parameters described herein can be used for creating artificial nanosystems that mimic the complexity observed in cell machinery.